Protective Effect of Artichoke (Cynara scolymus L.) Leaf and Receptaculum Extracts Against Hepatic Encephalopathy in Bile Duct Ligated Rats - Kam, Ozkan; Bebitoglu, Berna Terzioglu; Sener, Goksel; Oguz, Elif; Erdogan, Nurettin Fatih; Kilickap, Andac; Hatiboglu, Nebile (Springer/Plenum Publishers, 2025)
Hepatic encephalopathy (HE), complication of liver dysfunction, leads to neurocognitive impairments. Artichoke (Cynara scolymus L.) has been traditionally used for its antioxidant, anti-inflammatory and hepatoprotective properties. This study evaluates artichoke leaf and receptaculum extracts in cholestasis and HE in a rat model. Wistar rats were divided into 6 groups: sham-control, bile duct ligation (BDL), and BDL with low/high-dose leaf or receptaculum extracts. After BDL, physiological saline and extracts (250/500 mg/kg) were administered orally for 28 days. Cognitive activity was evaluated using Morris water maze and novel object recognition tests on day 28. Artichoke extract regulated liver enzymes and bilirubin at high-doses and significantly increased antioxidant enzyme activities reduced by BDL. Elevated 8-Hydroxyguanosine (8-OHdG) levels decreased in liver and brain tissues. Similarly, artichoke extracts reduced cytokine and hydroxyproline (HP) levels elevated by cholestasis. Following BDL, Na+/K+-ATPase levels in brain and liver tissues decreased, while artichoke extract reversed this. Artichoke, particularly high-dose receptaculum, improved impaired performance and increased time in the target quadrant after BDL. Both artichoke leaf and receptaculum extracts improved recognition. Artichoke treatments, especially high-dose receptaculum, reduced hepatic and neuronal damage and improved histological appearance. These findings highlight the therapeutic potential of artichoke extracts for liver fibrosis and related neurocognitive disorders.
Keywords: Artichoke; Bile Duct Ligation; Liver Fibrosis; Hepatic Encephalopathy